The Role Of Homeroom Teachers In Overcoming Bullying Behavior Among Fourth Grade Students At MIN 26 Aceh Utara - Wahyuni; Almuhajir; Samsul Bahri (putrapublisher.org, 2026)
This study aims to determine the role of homeroom teachers in overcoming bullying behavior among fourth-grade students at MIN 26 Aceh Utara. This research used a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The participants consisted of homeroom teachers, the school principal, and fourth-grade students. The results showed that homeroom teachers played an important role in overcoming bullying behavior through giving advice, supervision, character building, and personal approaches to students. The strategies applied included rotating students’ seating positions every week, providing special guidance for students involved in bullying, and instilling values of empathy and mutual respect through daily habituation activities at school. The forms of bullying found in this study included verbal bullying such as mocking parents’ names, physical appearance, and giving inappropriate nicknames, as well as physical bullying such as pushing, stepping on friends’ feet, and hitting during playtime. The challenges faced by teachers included repeated bullying behavior, students’ lack of awareness regarding the negative impacts of bullying, and limited teacher supervision during break times and outside learning hours. This study shows that cooperation between teachers, parents, and the school is very important in preventing and overcoming bullying behavior in schools.